NADI KEHIDUPAN - Harhy Safmitha Syafmal (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT The issue of shifting in togetherness values such as applied by Kubu people is impressed as something that its concept is contradictive toward current development. This reality has brought out a notion that becomes creator’s base in applying it to a dance choreography which talks about the individual concept in people’s life. Until today and without realizing about it, care toward others has not been an important thing in life anymore.The concept of movement is movement developed and explored through human’s behaviors namely the existence of a gap in the life process. Those behaviors exist because of stimulus from idea seen in the description of human’s individual concept toward others.This work is formulated into a comparison toward a life pattern based on togetherness of Kubu or Suku Anak Dalam people, and it is contradictory with a life process of humans in their environment that tends to be individual. Keywords: Life Pulse, Kubu, Togetherness, Dance Work